Phenotypic and Genotypic Characterization of mecA gene in Methicillin-Resistant Staphylococcus aureus with Detection of Homologous Sequences isolated from Hospital Acquired Infection Patients admitted at a Tertiary Care Hospital in Dhaka City of Bangl (Bangladesh Journal of Infectious Diseases, 2025)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) has become a major concern for public health. Compared to infections caused by methicillin-susceptible Staphylococcus aureus (MSSA), MRSA causes severe infections with increased morbidity and mortality and also places a large economic pressure on our health care sector.Objective: The purpose of the present study was to determine the prevalence of MRSA in different clinical samples isolated from admitted patients in a tertiary care hospital, Bangladesh.Methodology: This cross-sectional study was carried out in the Department of Microbiology at the Microbiology Laboratory of Dhaka Medical College, Dhaka, Bangladesh from January 2019 to December 2019 for a period of one year. Staphylococcus aureus was isolated from pus, wound swab and blood samples by culture, microscopy and different biochemical tests. MRSA were isolated by oxacillin and cefoxitin disc diffusion method using Kirby-Bauer technique and MIC of oxacillin by agar dilutional method. PCR and sequencing of mecA gene was done.Results: Out of 208 samples 42.2% MRSA and 57.78% MSSA were detected. Sensitivity and specificity of oxacillin disc diffusion method were 100% and 96.15%, respectively and for cefoxitin disc diffusion method both were 100% in comparison with MIC of oxacillin. All the 19 MRSA strains were positive for mecA gene.Conclusion: In conclusion there is a high prevalence of MRSA.Bangladesh Journal of Infectious Diseases, December 2024;11(2):146-151